2019
DOI: 10.2217/fvl-2018-0187
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of a Recombinant Baculovirus Displaying Anti-HER2 Scfv Expressing Apoptin in HER2 Positive SK-BR-3 Breast Cancer Cells

Abstract: Since HER2-targeted therapies have shown clinical benefit in breast cancer, in the present study recombinant baculovirus (BV) displaying anti-HER2 scFv expressing Apoptin was generated. Methods: The binding specificity and surface display of anti-HER2 scFv were evaluated using ELISA and electron microscopy, respectively. The targeting properties and cytotoxic effect on breast cancer cells determined by fluorescence microscopy and MTT assays. Results: The results demonstrated that recombinant BV could specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Recent researches have demonstrated that the negative feedback of Survivin was able to increase the apoptotic cells significantly when applied along with apoptin compared with treatment alone. 27 Another study reported that the integrated application of apoptin with interleukin-18 led to a severe Th1 immune response to Lewis lung carcinomas which resulted in significant growth inhibition of these tumor cells. 28 The most critical challenge in studies of apoptin is related to the development of a technique for efficient apoptin delivery to the tumor lesion site.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have demonstrated that the negative feedback of Survivin was able to increase the apoptotic cells significantly when applied along with apoptin compared with treatment alone. 27 Another study reported that the integrated application of apoptin with interleukin-18 led to a severe Th1 immune response to Lewis lung carcinomas which resulted in significant growth inhibition of these tumor cells. 28 The most critical challenge in studies of apoptin is related to the development of a technique for efficient apoptin delivery to the tumor lesion site.…”
Section: Discussionmentioning
confidence: 99%
“… 100 In comparison, rBVs displaying human epidermal growth factor-2 (HER2) single-chain variable domain fragments (scFV) while expressing Apoptin bind specifically HER2 positive SK-BR-3 breast cancer cells reducing cancer cell viability. 101 Similarly, a rBV expressing BIMs, a strong apoptosis inducer, resultedin selective death of HCV-positive cells only further proving BV’s potential for selective gene therapy. 102 The selective treatment of an individual’s malfunctioning or impaired cells can mitigate the systemic and adverse effects seen in traditional medical treatments, significantly improving the quality of treatment, care, and life.…”
Section: Application Of Baculoviruses In Gene and Other Therapiesmentioning
confidence: 99%
“…The expression of anti-HER2 allows the selective binding of baculovirus to tumor cells, since HER2 is a transmembrane receptor tyrosine kinase that is overexpressed in 30% of all cases of breast cancer and aggressive tumors. Once the baculovirus specifically enters cancer cells, apoptonin expression begins leading to tumor cell death [ 61 ].…”
Section: Introductionmentioning
confidence: 99%